Stress analysis in oral obturator prostheses: Imaging photoelastic - Pesqueira, Aldieris Alves [UNESP]; Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Haddad, Marcela Filié [UNESP]; Andreotti, Agda Marobo [UNESP]; Moreno, Amália [UNESP] (SPIE, the international society for optics and photonics, 2013)
Maxillary defects resulting from cancer, trauma, and congenital malformation affect the chewing efficiency and retention of dentures in these patients. The use of implant-retained palatal obturator dentures has improved the self-esteem and quality of life of several subjects. We evaluate the stress distribution of implant-retained palatal obturator dentures with different attachment systems by using the photoelastic analysis images. Two photoelastic models of the maxilla with oral-sinus-nasal communication were fabricated. One model received three implants on the left side of the alveolar ridge (incisive, canine, and first molar regions) and the other did not receive implants. Afterwards, a conventional palatal obturator denture (control) and two implant-retained palatal obturator dentures with different attachment systems (O-ring; bar-clip) were constructed. Models were placed in a circular polariscope and a 100-N axial load was applied in three different regions (incisive, canine, and first molar regions) by using a universal testing machine. The results were photographed and analyzed qualitatively using a software (Adobe Photoshop). The bar-clip system exhibited the highest stress concentration followed by the O-ring system and conventional denture (control). Images generated by the photoelastic method help in the oral rehabilitator planning. © 2013 SPIE.
Keywords: dental implant; maxillectomy; photoelasticity; Adobe Photoshop; Circular polariscope; Congenital malformations; Photo-elastic analysis; Photoelastic method; Photoelastic models; Universal testing machines; O rings; Photoelasticity; Stress analysis; Stress concentration; Dental prostheses; dental procedure; elasticity; maxillofacial prosthesis; mechanical stress; palatal obturator; photography; prosthesis; Dental Models; Elasticity; Maxillofacial Prosthesis; Palatal Obturators; Photography; Prosthesis Design; Stress, Mechanical